2021
DOI: 10.1159/000512599
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Abnormalities in the Basal Ganglia of Dystonia Patients

Abstract: <b><i>Objective:</i></b> The pathophysiology of dystonia is poorly understood. As opposed to secondary forms of dystonia, primary dystonia has long been believed to lack any neuroanatomical substrate. During trajectory planning for DBS, however, conspicuous T2-hyperinstensive signal alterations (SA) were registered within the target region, even in young patients, where ischemia is rare. <b><i>Methods:</i></b> Fifty MRIs of primary dystonia patients scheduled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…A stronger magnetic field (measured in tesla, T) provides higher signal to noise ratio, enabling higher image resolution; however, stronger fields are limited by faster signal loss, exacerbation of inhomogeneities within the field (which can distort the measured signal) and potential tissue heating due to differing radiofrequency requirements. The studies identified used either 1.5 T ( n = 16) [9–24] or 3 T ( n = 57) strength.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A stronger magnetic field (measured in tesla, T) provides higher signal to noise ratio, enabling higher image resolution; however, stronger fields are limited by faster signal loss, exacerbation of inhomogeneities within the field (which can distort the measured signal) and potential tissue heating due to differing radiofrequency requirements. The studies identified used either 1.5 T ( n = 16) [9–24] or 3 T ( n = 57) strength.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the volumetric studies, spatial resolution is important, with smaller voxel sizes reducing partial volume effects and enhancing delineation of anatomical borders, resulting in more accurate volumetric measures. Specifically, amongst the volumetric studies, the majority had dimensions of ≤1 mm 3 ( n = 27), with the rest having a maximum dimension of 1–1.5 mm ( n = 7) [17, 22, 24–28], 1.5–2 mm ( n = 1) [16] or not stated ( n = 4) [14, 29–31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations